Designing ICT Competences-Integrated Syllabuses of Research Skills Professional Administration Courses - Begovic Yahya, Aliya Izet; Dewanti, Ratna; Sulistyaningrum, Drivoka (Riviera Publishing, 2023)
ICT has affected all aspects of life and has been used extensively in all sectors of human life, including Education. Integrating ICT into learning is one of the ICT implementations in the educational aspect. Therefore, one of the critical competencies of an educator in improving his professional abilities is Research Skills and Professional Administration courses in Education. This study designs the integration of ICT in the syllabuses of Research Skills and Professional Administration Courses. This study aimed to design the syllabuses for Research Skills and Professional Administration Courses based on integrated ICT competencies for the English Study Program. This study used Design and Development Research (DDR) as the research design and qualitative research methods. The stages used by DDR in this study are Need Analysis, Designing Preliminary Research, Evaluation, Revision and Design of Prototype Syllabus. This analysis involves ICT competencies proposed by UNESCO, Digital Media Descriptors from the European Profiling Grid (EPG) and other ICT-based theories. This study found that ICT competencies were integrated mainly into Learning Outcomes, Teaching Methods, Learning Activities and Assessments explicitly or implicitly. The study provides ICT integration procedures and designs the syllabuses of Research Skills and Professional Administration Courses; Introduction to Research Methodology, English Language Research Methodology and Professional Education in Administration. The resulting syllabus design is Content Based Syllabus which is product oriented.